FACTORS THAT AFFECT THE BUDGET ABSOPTION IN LOCAL GOVERNMENT WORK UNIT OF THE CITY OF MEDAN WITH THE GOVERNMENT INTERNAL CONTROL SYSTEM AS A MODERATING VARIABLE - asniarti, asniarti (International Journal of Public Budgeting, Accounting and Finance, 2020)
This study aims to analyze the effect of Budget Implementation Document (BID) quality, HR quality, bureaucratic reform and organizational commitment to the absorption of Local Government Work Unit budget of Medan City Government with the internal control system of the government as a moderating variable. This type of research is causality. The population in this study were all Local Government Work Unit of Medan City Government, which amounted to 54 (fifty four) Local Government Work Units. The sampling technique uses a purposive sampling method, so that those who meet the criteria to be used as research samples are 33 (thirty three) Local Government Work Units with 66 observations consisting of 66 (sixty six) respondents consisting of the Head of the Local Government Work Unit and the Head of Financial Subdivision Local Government Work Unit. The data of this study were analyzed using Structural Equation Modelling Partial Least Squares (SEM PLS). The results showed that the quality of BID, the quality of human resources, bureaucratic reform had a significant positive effect on budget absorption and organizational commitment had a positive effect but not significantly on budget absorption. The government internal control system as a moderating variable cannot moderate the relationship between BID quality, HR quality, bureaucratic reform and organizational commitment to budget absorption in Local Government Work Unit of Medan City Government.